Pemberdayaan Masyarakat Melalui Program Kkn Tematik Di RT 21 RW 05 Kelurahan Sawah Lebar - Caya, Ayang Putri; Hartina, Egidia; Wulandari, Putri; Sundari, Gita Putri; Kurniawan, Irfan; Fadilla, Rohayu; Lorita, Evi; Rullyanti, Merry (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Thematic Community Service Program is a community service program aimed at providing real solutions to problems faced by society. This KKN-T program wasconducted in RT 21 RW 05 SawahLebarVillage with a focus on improving environmental quality, administrative services, and community awareness. The main problems identified include waste accumulation, lack of visual education facilities, absence of digital population database systems, and insufficient public green spaces. Implementation methods include field surveys, Focus Group Discussions, mutual cooperation, creation of educational media, data digitization, and garden development. The results show significant improvements in environmental cleanliness, availability of digital databases, installation of road signs, and creation of Tapak Jedah Garden as a public space. The conclusion showsthat collaborationbetweenstudents, supervisors, and communitysuccessfully created sustainable positive changes inthe target area